A Relationship Governance Perspective of Organizational Buyers' Supplier Choice Decisions. Issue 4 (2nd October 2017) - Gao, Tao (Tony)
ABSTRACT: Although the transaction cost analysis (TCA) has long been used by marketing and management scholars to study organizational buyers' make-or-buy decisions, it sheds limited light on their choice behavior beyond the make-or-buy trade-off. In the meantime, many organizational purchase decisions are structured around which independent supplier to buy from, rather than a typical make-or-buy decision. This study extends existing research on TCA by applying this theoretical framework to explore why organizational buyers make purchases from among independent suppliers. The article posits that (1) two forms of relationship governance—buyer trust and market (i.e., the relative dependence between the buyer and supplier)—help explain the differences in buyer decision-making uncertainty involving independent suppliers, which further influences the buyers' propensity to purchase; and that (2) trust further influences the buyers' propensity to purchase due to its effect on customer perceived value. The empirical study based on organizational purchasing decisions lends support to the predictions of the relationship governance theory.